The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s13197-018-3178-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple responses optimization of instant dark tea production by submerged fermentation using response surface methodology

Abstract: In this study, submerged fermentation mode for preparing instant dark tea production was developed through utilizing industrial low grade green tea as raw material and as fermentation microbe starter. The fermentation parameters (inoculum size, liquid-solid ratio and rotation speed) were optimized by using Box-Behnken design and response surface methodology (RSM) with desirability function, the theabrownins content, redness and turbidity value as responses. The optimal conditions were set as follow: inoculum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These data indicated that A. tubingensis could efficiently utilize TPs and catalyze the transformation from TPs to TFs and TBs, while A. cristatus had a weak ability to catalyze the oxidation of TPs but consumed the highest contents of TPs in IDTs fermented by fungi. Our study showed that the mellow mouthfeel of IDTs would better format with the degradation of TPs and the formation of tea pigments under the action of microorganisms ( Wang Y. et al, 2018 ).…”
Section: Resultsmentioning
confidence: 90%
“…These data indicated that A. tubingensis could efficiently utilize TPs and catalyze the transformation from TPs to TFs and TBs, while A. cristatus had a weak ability to catalyze the oxidation of TPs but consumed the highest contents of TPs in IDTs fermented by fungi. Our study showed that the mellow mouthfeel of IDTs would better format with the degradation of TPs and the formation of tea pigments under the action of microorganisms ( Wang Y. et al, 2018 ).…”
Section: Resultsmentioning
confidence: 90%
“…The response surface optimization experiments were based on Wang's method and slightly modified [24]. Based on the single factor experiments, the software design response surface experiment was designed, and the factors and levels are shown in Table 1.…”
Section: Response Surface Optimization Experimentsmentioning
confidence: 99%
“…Therefore, the production of many famous green teas has certain requirements for varieties. For example, Anji white tea, a green tea produced from the ‘ Baiye1 ’ tea variety, has high umami and low bitterness and astringency because of its high free amino acid content and low polyphenolic content ( Wang, Zhang, Chen, & Jiang, 2020 ; Yan et al, 2017 ). Taiping Houkui tea, produced from ‘ Shidacha ’, has a strong orchid aroma and a mellow flavor ( Zhou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%